INTERNALISASI NILAI-NILAI KEISLAMAN DALAM PENCEGAHAN KHAMAR PADA KALANGAN REMAJA - Hidayat, Rahmat; Lismawati, Lismawati (ITB AAS Indonesia Surakarta, 2024)
Alcoholic beverages, or khamr, contain alcohol or ethanol and were originally made from dates and grapes. In the Islamic religion, khamr is considered haram. A study was conducted to reveal views on the prohibition of khamr, prevention efforts, and the health benefits of the ban for adolescents. Religious figures were involved in data collection. A religious approach has been used to educate adolescents, such as through adolescent health posts, youth organizations, and mosque youth groups. Emphasizing Islamic values in adolescents’ daily lives is believed to shape good morals. Internalizing Islamic values also helps prevent the consumption of alcoholic beverages, which can have negative effects on adolescent health. Therefore, religious activities such as pengajian (religious studies) and children’s forums are considered effective ways to prevent alcohol consumption among adolescents.